Theoretical analysis of the kinetics of low-temperature defect recombination in alkali halide crystals - Kuzovkov, V.N.; Popov, A.I.; Kotomin, E.A.; Moskina, A.M.; Vasil`chenko, E.; Lushchik, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We analyzed carefully the experimental kinetics of the low-temperature diffusion-controlled F, H center re-combination in a series of irradiated alkali halides and extracted the migration energies and pre-exponential parameters for the hole H centers. The migration energy for the complementary electronic F centers in NaCl was obtained from the colloid formation kinetics observed above room temperature. The obtained parameters were compared with data available from the literature.